2014
DOI: 10.1016/j.biomaterials.2014.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Turning a water and oil insoluble cisplatin derivative into a nanoparticle formulation for cancer therapy

Abstract: The formulation of water insoluble organic compounds into nanoparticles has become a widely established method for enhancing the delivery and efficacy of cancer therapeutics. Therefore, a comparable approach when applied to water insoluble inorganic compounds should also promote similar advantages. Herein, we have successfully formulated insoluble iodinated cisplatin (CDDP-I) into a LPI NPs (lipid-coated iodinated CDDP nanoparticles). Two separate microemulsions were combined, each containing a precursor for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…26 Briefly, 200 mM cis-[Pt(NH 3 ) 2 (H 2 O) 2 ](NO 3 ) 2 and 800 mM KCl in water were separately dispersed in a solution composed of Cyclohexane/Igepal CO-520 (71:29, V:V) and Cyclohexane/Triton-X100/Hexanol (75:15:10, V:V:V) (3:1) to form a well-dispersed, water-in-oil reverse micro-emulsion. One hundred μL DOPA (20 mM) was added to the CDDP precursor phase and the mixture was stirred.…”
Section: Methodsmentioning
confidence: 99%
“…26 Briefly, 200 mM cis-[Pt(NH 3 ) 2 (H 2 O) 2 ](NO 3 ) 2 and 800 mM KCl in water were separately dispersed in a solution composed of Cyclohexane/Igepal CO-520 (71:29, V:V) and Cyclohexane/Triton-X100/Hexanol (75:15:10, V:V:V) (3:1) to form a well-dispersed, water-in-oil reverse micro-emulsion. One hundred μL DOPA (20 mM) was added to the CDDP precursor phase and the mixture was stirred.…”
Section: Methodsmentioning
confidence: 99%
“…This could be explained by the active targeting ability of FA which could cell internalization through specific FRs on the surface of MCF-7 cells (Wu et al, 2014). The results also indicated that the enhanced permeability and retention (EPR) effect could appeared effect in highly fenestrated tumor endothelial cells, uptake of NLCs by MCF-7 cells might be enhanced by across the cell membrane via endocytosis or direct penetration may enhance intracellular drug accumulation (Guo et al, 2014).…”
Section: Characterization Of Fa-cur-nlcsmentioning
confidence: 85%
“…This was attributed due to the active targeting potential of folic acid, which can internalize through specific folate receptors present on the surface of MCF-7 cells. Enhanced cellular uptake of NLCs by MCF-7 cells may be attributed though the cell membrane via endocytosis or direct penetration may enhance intracellular drug accumulation (Guo et al, 2014). Liu et al (2015) have actively targeted breast tumors using Hyaluronic acid for delivery of Baicalein and Doxorubicin.…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%